Diagnóstico de la satisfacción del servicio que brinda el área de pediatría consulta externa del Hospital Aníbal González Álava del Cantón Bolívar - Pilligua Vera, María Gabriela (2018)
The objective of the research was to diagnose the satisfaction level of the users with the service provided by the pediatric area, external consultation of the Dr. Aníbal González Álava Hospital. The methodology used was the servqual survey model that evaluates five dimensions to determine the gaps between perceptions and expectations; the instrument was applied to 46 users. The quantitative data processing was done in Microsoft Excel and statistical equations, in addition with the inductive-deductive method the analysis was made for the qualitative assessment in a continuous scale that qualified the results as: very dissatisfied, dissatisfied, moderately satisfied, satisfied or very satisfied. The overall result was satisfactory, however, at the level of indicators, it was determined that there are affectations in the modernity of medical equipment, the service response, scheduling by appointment, waiting time, compliance with the schedules and the staff's concern for the patient's interests; so it was considered an administrative intervention through the proposal of an improvement plan, which was socialized with the area administrator and with its application helps to guarantee the universal right of people to access a timely health service, with quality and warmth